(untitled) (Altre Modernità, 2019)
This article presents a map of the linguistic accessibility of the 54 Italian Heritage Sites of UNESCO for the Spanish-speaking visitors with the aim of highlighting the potential of translation as a tool for tourism promotion and reception, since Italy represents the third favourite destination of the Spanish after France and Portugal (ONT 2012). The research is based on the analysis of the UNESCO official websites as well as the pages of the regions, provinces and municipalities where the Italian World Heritage Sites are located. The quality of the translation was also analysed following criteria such as: syntactic and orthographic correction, fidelity in the transposition of the content, stylistic adaptation, readability and quality of the editing. The results show that the linguistic accessibility of the UNESCO Heritage Sites in Spanish is still low because the translation into a cognate language is underestimated either by preferring the translation in English or by committing it to an automatic translator.